2018
DOI: 10.1111/cge.13236
|View full text |Cite
|
Sign up to set email alerts
|

A B3GALT6 variant in patient originally described as Al‐Gazali syndrome and implicating the endoplasmic reticulum quality control in the mechanism of some β3GalT6‐pathy mutations

Abstract: Al-Gazali syndrome encompasses several clinical features including prenatal growth retardation, large joints contractures with camptodactyly, bilateral talipes equinovarus, small mouth, anterior segment anomalies of the eyes, and early lethality. Recently, a baby with features very similar to Al-Gazali syndrome was found to have compound heterozygous variants in B3GALT6. This gene encodes Beta-1,3-galactosyltransferase 6 (β3GalT6), an essential component of the glycosaminoglycan synthesis pathway. Pathogenic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The radiological findings are undoubtedly the most significant evidence in distinguishing B4GALT7 -related and B3GALT6 -related spEDS: the latter includes more numerous and pronounced elements of skeletal dysplasia, and for this reason has often been classified as such in the past. Radioulnar synostosis has been observed recurrently and almost exclusively in spEDS- B4GALT7 (19/32 cases, including our patient, vs 3 documented cases of spEDS- B3GALT6 [53,56]. On the other hand, most of the individuals affected by B3GALT6 -related spEDS, including our patients, display severe kyphoscoliosis, usually congenital or early onset and progressive (36/39), and several of the skeletal changes associated with SEMDJL1, such as platyspondyly, short iliac bones, elbow dislocation with misalignment of the long bones (33/36).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The radiological findings are undoubtedly the most significant evidence in distinguishing B4GALT7 -related and B3GALT6 -related spEDS: the latter includes more numerous and pronounced elements of skeletal dysplasia, and for this reason has often been classified as such in the past. Radioulnar synostosis has been observed recurrently and almost exclusively in spEDS- B4GALT7 (19/32 cases, including our patient, vs 3 documented cases of spEDS- B3GALT6 [53,56]. On the other hand, most of the individuals affected by B3GALT6 -related spEDS, including our patients, display severe kyphoscoliosis, usually congenital or early onset and progressive (36/39), and several of the skeletal changes associated with SEMDJL1, such as platyspondyly, short iliac bones, elbow dislocation with misalignment of the long bones (33/36).…”
Section: Discussionmentioning
confidence: 65%
“…Their recent classification as spEDS [46] provides a valid assistance for their diagnosis, but the observation of new patients and the study of the clinical signs of those already reported in the literature can further improve our knowledge. In an effort to better define both the similarities and the peculiarities of these syndromes, we reviewed the notable features of our three patients and compared them to those of molecularly confirmed B4GALT7 - and B3GALT6 -related cases reported in the literature (Table 1 and Table 2) [18,21,22,23,24,29,30,31,32,33,44,45,48,51,52,53,54,55,56]…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Malfait et al (2013 ) and Nakajima et al (2013 ) reported B3GALT6 pathogenic variants in human diseases. Since then, dozens of B3GALT6 variants in the recessive status have been identified in approximately 40 unrelated families with Ehlers–Danlos syndrome (EDS) ( Sellars et al, 2014 ; Vorster et al, 2015 ; Alazami et al, 2016 ; Trejo et al, 2017 ; Ben-Mahmoud et al, 2018 ; Van Damme et al, 2018 ; Caraffi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme has a preference for galactose‐beta‐1,4‐xylose that is found in the linker region of GAGs, such as heparan sulfate and chondroitin sulfate (https://www.uniprot.org/uniprot/Q96L58). Biallelic mutations in the B3GALT6 gene have been reported to cause a variable clinical spectrum, with at least three recognizable multisystemic disorders with overlapping but distinctive musculoskeletal involvement represented by spondyloepimetaphyseal dysplasia with joint laxity type 1 (SEMDJL1, also known as SEMDJL Beighton type), B3GALT6‐related spondylodysplastic Ehlers‐Danlos syndrome (spEDS_B3GALT6), formerly type 2 spondylodysplastic Ehlers‐Danlos syndrome (EDSSPD2), and Al‐Gazali syndrome (ALGAZ) (Ben‐Mahmoud et al, 2018; Malfait et al, 2017; Mortier et al, 2019; Nakajima et al, 2013). Nakajima and co‐authors first identified biallelic pathogenic variants cosegregating with SEMDJL1 and spEDS_B3GALT6 in two small cohorts of Eastern Asian families, underlying the pleiotropic consequences of defective Beta3GalT6 function on processes controlling the development and physiology of skin, bone, tendons, and ligaments (Nakajima et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Malfait and collaborators also reported B3GALT6 mutations in five patients from three Iranian families (Malfait et al, 2013), all affected with a multisystemic disorder characterized by connective tissue fragility, early‐onset bone fractures, spondyloepimethaphyseal dysplasia, and intellectual disability. More recently, ALGAZ was recognized as a disorder caused by dysfunctional Beta3GalT6 and characterized by prenatal growth retardation, skeletal anomalies, small mouth, anterior segment eye anomalies, and early lethality (Ben‐Mahmoud et al, 2018).…”
Section: Introductionmentioning
confidence: 99%